Detecting Atrial Fibrillation Using Smartwatches - Agnieszka Kulczycka-Rowicka; Julianna Podolec; Silvia Ciraolo; Joanna Wojda; Adam Sobiński; Zuzanna Kościuszko; Katarzyna Kurza; Matylda Czerwonka; Katarzyna Lesiczka-Fedoryj; Anna Walczak (Quality in Sport)
The purpose of research: